KAJIAN KONSERVASI TANAH KRITIS BERDASARKAN SATUAN LAHAN DI DAERAH TANGKAPAN AIR SEMPOR KABUPATEN KEBUMEN - Dwi Priyo Ariyanto; Bambang Hendro Sunarminto; Dja’far Shiddieq (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Study of Critical Soil Conservation Based on Land Unit on Sempor’s Catchment Area, Kebumen Regency. This research  aims to predict critical soil and soil erosion  level of Sempor’s  Catchment Area and to recommend the management according to soil conservation.This  is  an  explorative  descriptive  research  based  on  environment  data.  The  data  are obtained from field observation and result of laboratory analysis of soil samples taken from field survey. Furthermore, the data are classified based on critical soil classification to get critical soil map. The data also are calculated based on USLE to get soil erosion prediction. The results of soil erosion prediction are grouped based on erosion hazard levels and result of soil erosion mapping. After knowing  critical soil and soil erosion level in each land unit, recommendation  is made to manage land according to soil conservation.The result shows that on observation area with total extent 4,333.68 ha there are criticalsoil about 1,373.68  ha (31.70 %), semi critical about 2,164.54  ha (49.95 %), potentially  critical about 440.46 ha (10.16 %) and the others are about 355.00 ha (8.19 %) in the form of settlement and  reservoir  located  at  the  outside  of  the  observation  area.  The  soil  erosion  predicted  on observation area are divided into 6 classes, those are very low erosion class at about 103.90 ha (2.40 %), low erosion class at about 332.00 ha (7.66 %), moderate erosion class at about 953.78 ha (22.01 %), high erosion class at about 247.53 ha (5.71 %), very high erosion class at about 2,108.50 ha (48.65 %), acute erosion class at about 232.96 ha (5.38 %) and the others are out of observation  area. Topography  and land management  are factors that have the most dominant influence to soil erosion prediction. Total soil erosion on observation  area is about 320,958.016 tons/ha  or soil erosion average  about 74.061 tons/ha/year.  The recommendation  is to restore critical and erosion through some actions such as reboization or planting with annual crop, vegetation nursery, adding organic matter via organic fertilizer or organic mulches, making and maintaining of terrace and ditches, and agroforestry.Keywords: critical soil, erosion, Sempor,  soil coservation